Developing the Bilingual Competence in Learning Foreign Languages - T. A. Znamenskaya (Russian State Vocational Pedagogical University, 2015)
The paper considers the problem of bilingualism and its effect on the personality of the speaker. Various types of bilingualism are described along with the factors determining the bilingual competence formation: age, individual experience, socio-cultural conditions of the native and foreign language interaction. The author points out both the positive and negative impact on the native language as the result of the second language learning. The special emphasis is on language interference in the process of learning a foreign language. To make sure the students achieve the adequate degree of its authenticity, and therefore the bilingual competence, the teacher should take into account the specificity of national styles, communicative strategies and speech tactics of both languages. A comparative analysis of linguistic differences of the English and Russian languages is demonstrated on the level of phonetics, vocabulary, grammar and national communicative stylistics. The author maintains that successful inter-language and cross-cultural communication requires the integrative cross-disciplinary approach, consolidation of the linguistic theory and methods of foreign language teaching.